2012
DOI: 10.5665/sleep.2012
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Problems: An Emerging Global Epidemic? Findings From the INDEPTH WHO-SAGE Study Among More Than 40,000 Older Adults From 8 Countries Across Africa and Asia

Abstract: A large number of older adults in low-income settings are currently experiencing sleep problems, which emphasizes the global dimension of this emerging public health issue. This study corroborates the multifaceted nature of sleep problems, which are strongly linked to poorer general well-being and quality of life, and psychiatric comorbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
342
8
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 485 publications
(380 citation statements)
references
References 48 publications
23
342
8
7
Order By: Relevance
“…Previous research has demonstrated that sleep has no clear relationship with either a country's gross domestic product or a household's income in transitioning populations (Mazzotti et al, 2012; Stranges et al, 2012). This suggests that sleep is relatively independent of economic strategy in populations undergoing the rapid and wide‐reaching changes associated with economic transition.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Previous research has demonstrated that sleep has no clear relationship with either a country's gross domestic product or a household's income in transitioning populations (Mazzotti et al, 2012; Stranges et al, 2012). This suggests that sleep is relatively independent of economic strategy in populations undergoing the rapid and wide‐reaching changes associated with economic transition.…”
Section: Discussionmentioning
confidence: 98%
“…Because age and gender have a consistent relationship with sleep complaints (Bilwise, 1993; Walsleben, 2011; Mazzotti et al, 2012; Stranges et al, 2012), they were the only predictors included in the first step of the regression. The second step added the socio‐demographic variables that were significant or tended toward significance ( P  < 0.10) in simple bivariate comparisons.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations